2014
DOI: 10.1115/1.4026641
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Consistency of Handwriting Grip Kinetics in Adults

Abstract: While there is growing interest in clinical applications of handwriting grip kinetics, the consistency of these forces over time is not well-understood at present. In this study, we investigated the short- and long-term intra-participant consistency and inter-participant differences in grip kinetics associated with adult signature writing. Grip data were collected from 20 adult participants using a digitizing tablet and an instrumented pen. The first phase of data collection occurred over 10 separate days with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Force measuring films have been shown to be suitable for measuring the grip forces and position of individual fingers 33 , 34 as well as their dynamics during movement 35 . Findings from writing studies have shown that applying these films on a pen is possible 36 , 37 . Therefore, it is recommended that such systems are used in the future to further elucidate the forces during the drawing behavior of MCI men.…”
Section: Discussionmentioning
confidence: 99%
“…Force measuring films have been shown to be suitable for measuring the grip forces and position of individual fingers 33 , 34 as well as their dynamics during movement 35 . Findings from writing studies have shown that applying these films on a pen is possible 36 , 37 . Therefore, it is recommended that such systems are used in the future to further elucidate the forces during the drawing behavior of MCI men.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of handwriting grip kinetic variability in the adult population is very limited [3]. Recently, we studied the variability of grip kinetics associated with signature writing in adults [1,13] and found that the variability of kinetic topographies (i.e., grip shape) between individuals was much higher than the variability within an individual, even when considering signatures collected over several months. These findings encouraged the study of variations in a summative handwriting grip kinetic profile, which is the time series of total force variation over the course of a signature.…”
Section: Introductionmentioning
confidence: 99%